Arguments in Indonesian and Chinese Students’ English Argumentative Essays: Spotlighting The Quality and Gender - Abdullah, Fuad; Siregar, Bahren Umar; Tandiana, Soni Tantan (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2025)
Various studies have examined argumentative writing from multiple perspectives. However, the quality of arguments in Indonesian and Chinese students’ English argumentative essays, particularly when analyzed from both quality and gender perspectives, remains underexplored. Hence, this study aims to address this gap by investigating the quality of argumentation and gender related patterns in English argumentative essays produced by Indonesian (IDN) and Chinese (CHN) learners of English. The corpus consisted of 20 English argumentative essays on the same topic, namely non-smoking, which were purposively selected from the International Corpus Network of Asian Learners of English (ICNALE). The essays were grouped based on students’ nationalities into Indonesian and Chinese categories. The data were analyzed using the Argumentation Quality Evaluation proposed by Erduran et al. (2004) and the Thematic Analysis developed by Braun and Clarke (2006) to examine the quality and thematic patterns of the arguments. The findings indicate that Indonesian and Chinese students’ English argumentative essays demonstrated varying levels of argument quality, from weak to strong. Regarding gender, the results show that both male and female students from the Indonesian and Chinese groups produced comparable argument structures, suggesting no substantial gender-based differences in the construction of arguments. The pedagogical implications of this study provide insights for TESOL practitioners, learners of English as a foreign language, policymakers, and linguists by emphasizing the importance of developing students’ awareness of argumentative structures and strengthening their ability to evaluate the quality of arguments in English argumentative writing.  Abstrak Meskipun banyak sekali penelitian telah dilaksanakan untuk mengkaji tulisan argumentatif dari berbagai sudut pandang, bagaimana argumen dalam esai argumentatif bahasa Inggris mahasiswa Indonesia dan Tiongkok dari sudut pandang kualitas dan gender masih kurang dipelajari. Oleh karena itu, penelitian ini bertujuan untuk mengisi kekosongan tersebut. Korpus penelitian ini terdiri dari 20 esai argumentatif dengan topik yang sama, yakni non-merokok dan dipecah menjadi dua kelompok berdasarkan kewarganegaraan mahasiswa, seperti Indonesia (IDN) dan Tiongkok (CHN). Korpus ini dikumpulkan secara terpilih melalui analisis dokumen dari situs web International Corpus Network of Asian Learners of English (ICNALE) sebagai basis korpus dan dianalisis dengan Evaluasi Kualitas Argumentasi (Erduran et al., 2004) dan Analisis Tematik (Braun dan Clarke, 2006). Temuan mengungkapkan bahwa esai argumentatif bahasa Inggris mahasiswa Indonesia dan Tiongkok menunjukkan kualitas argumen yang lemah dan kuat. Terkait gender, temuan menguraikan struktur argumen yang sama yang dihasilkan oleh mahasiswa dan mahasiswi Indonesia dan Tiongkok. Implikasi pedagogis dari penelitian ini menawarkan informasi praktis bagi praktisi TESOL, mahasiswa bukan penutur asli bahasa Inggris, pembuat kebijakan dan linguis tentang pentingnya mengadaptasi kesadaran mahasiswa terhadap skema argumentatif dan evaluasi kualitas argumentasi saat menyusun esai argumentatif bahasa Inggris.